Particle number concentrations near the Rome-Ciampino city airport. (December 2016) - Stafoggia, M.; Cattani, G.; Forastiere, F.; Di Menno di Bucchianico, A.; Gaeta, A.; Ancona, C.
Abstract: Human exposure to ultrafine particles (UFP) has been postulated to be associated with adverse health effects, and there is interest regarding possible measures to reduce primary emissions. One important source of UFP are airport activities, with aircraft take-offs being the most relevant one. We implemented two measurement campaigns of total particle number concentrations (PNC), a proxy for UFP, near a medium-size airport in central Italy. One-minute PNC averages were collected on June 2011 and January 2012 concurrently with 30-min average meteorological data on temperature and wind speed/direction. Data on minute-specific take-offs and landings were obtained by the airport authorities. We applied statistical regression models to relate PNC data to the presence of aircraft activities while adjusting for time trends and meteorology, and estimated the increases in PNC ±15 min before and after take-offs and landings. We repeated the analyses considering prevalent wind direction and by size of the aircraft. We estimated PNC increases of 5400 particles/cm 3 /minute during the 15 min before and after take-offs, with a peak of 19, 000 particles/cm 3 /minute within 5 min after take-offs. Corresponding figures for landings were 1300 and 1000 particles, respectively. The highest PNC estimates were obtained when the prevailing wind came from the runway direction, and led to estimated PNC increases of 60, 000 particles/cm 3 /minute within 5 min after take-offs. No main differences were noted from the exhaust of different types of aircrafts. The area surrounding Ciampino airport is densely inhabited, raising concerns about the potential adverse effects of long-term and short-term exposure to airport-borne UFP. A close monitoring of airport activities and emissions is mandatory to reduce the public health impact of the airport on the nearby population. Highlights: An extensive campaign of minute-specific PNC implemented in Ciampino Airport, Italy. PNC increase by ∼20, 000 particles/cm 3 /minute in the 5 min after take-offs. PNC increases are three times larger when prevalent wind from the airport runway. Large resident population, with potential health impacts from airport-generated PNC.